Элементы современной математической физики учебное пособие для вузов - Багров физик профессор Томского государственного университета; Белов; Задорожный математик доцент Томского политехнического университета, кандидат физико-математических наук; Трифонов российский физик, математик профессор Томского политехнического университета, доктор физико-математических наук (Изд-во ТПУ, 2012)
This textbook presents supplementary chapters to the course "Methods of Mathematical Physics" and contains a material on special sections of this course: Calculus of Variations and its applications in classical mechanics; First-Order Partial Differential Equations; the Sturm-Liouville problem for partial differential equations, and pseudoVdifferential operators. The textbook can be useful to the graduate students, magisters, and postgraduates specializing in theoretical and mathematical physics. The textbook is intended for students and post-graduates of physical and engineering departments.